Immunogenicity and Efficacy of Pneumococcal Conjugate Vaccine (Prevenar13®) in Preventing Acquisition of Carriage of Pneumococcal Vaccine Serotypes in Tanzanian Children With HIV/AIDS - Makenga, Geofrey; Mtove, George; Yin, J. Kevin; Mziray, Abubakary; Bwana, Veneranda M.; Kisinza, William; Mjema, Julius; Amos, Ben; Antony, Laura; Shingadia, Delane; Oftadeh, Shahin; Booy, Robert (Frontiers in Immunology, 2021)
In every year, up to one million children die due to pneumococcal disease. Children infected with Human Immunodeficiency Virus (HIV) are mostly affected, as they appear to have higher rates of pneumococcal carriage and invasive disease. Successful immunity is dependent on mounting a sufficient immune response to the vaccine. We conducted a double blinded crossover randomised controlled trial to determine the serum antibody response (>4-fold and geometric mean concentration) to pneumococcal vaccine (PCV13) serotypes at 3 months after second vaccination. We also determined the number and proportion of children carrying new (not present at baseline) vaccine serotypes of S. pneumoniae isolated from nasopharynx at 6 months post initial vaccination in recipients of Prevenar13® compared with those given Haemophilus influenzae-type b (Hib) vaccine (control). The study was conducted at Teule Hospital in Muheza, Tanga Tanzania. 225 HIV infected children aged 1-14 years were enrolled from Jan 2013 to Nov 2013 and randomised to Prevenar13® or Hib vaccines each given at baseline and 2-3 months later. Nasopharyngeal and serum samples were collected at baseline and 4-6 months later. Serotyping was done by Quellung Reaction using Staten antisera. Serum antibodies were ELISA quantified. The study revealed a non-significant reduction in the acquisition of new vaccine serotypes of S. pneumoniae in the recipients of PCV13 by nearly a third compared to those who received Hib vaccine. The vaccine efficacy was 30.5% (95% confidence interval [CI] –6.4-54.6%, P=0.100)]. The antibody response was not enough to induce a 4-fold rise in GMC in 7 of the 13 vaccine serotypes. When combining the effects of preventing new acquisition and clearing existing vaccine type carriage, the overall efficacy was 31.5% (95% CI 1.5-52.4%, P=0.045). In the PCV13 group, the proportion of participants carrying vaccine serotype was significantly lower after 2 doses of PCV13 (30%; 32/107), compared with the baseline proportion (48%; 51/107). The introduction of PCV13 targeting HIV-positive children in a setting similar to Tanzania is likely to be associated with appreciable decrease in the acquisition and carriage of pneumococci, which is an important marker of the likely effect of the vaccine on pneumococcal disease.